Bioavailable IGF-1 and its relationship with endothelial damage in a bi-ethnic population: The SABPA study. Issue 5 (November 2015) - Koegelenberg, A.S.E.; Schutte, R.; Smith, W.; Schutte, A.E.
Abstract: Introduction: Insulin-like growth factor-1 (IGF-1) has vasculoprotective effects and can directly oppose endothelial dysfunction in several ways. To improve our understanding on the potential contribution of reduced IGF-1 to the development of vascular endothelial damage, we investigated the link between bioavailable IGF-1 and von Willebrand factor (vWF) as a marker of endothelial damage. We performed this study in black South African school teachers, known to be prone to hypertension. Materials and methods: From the larger Sympathetic activity and Ambulatory Blood Pressure in Africans (SABPA) study we included 179 black and 207 white non-diabetic men and women (aged 44.5 ± 9.96 years). We measured ambulatory blood pressure and determined IGF-1, insulin-like growth factor binding protein 3 (IGFBP-3) and vWF antigen from blood samples. We used the molar IGF-1/IGFBP-3 ratio as an estimate of bioavailable IGF-1. Results: Black individuals presented higher blood pressure and vWFag and lower IGF-1 than the white group (all p < 0.001). In multivariate-adjusted analyses, vWFag was inversely associated with IGF-1 (R 2  = 0.18; β = − 0.17; p = 0.044) and IGF-1/IGFBP-3 (R 2  = 0.18; β = − 0.17; p = 0.030) in blacks, with no associations in whites. Since IGF-1 is attenuated and vWFag elevated in diabetes, we included patients with diabetes (n = 38) and the aforementioned associations found in blacks remained robust. Conclusion: The inverse association between bioavailable IGF-1 and vWF in black South Africans suggests that suppressed IGF-1 may result in endothelial damage independent of traditional risk factors. Highlights: Blacks presented higher blood pressure and von Willebrand factor antigen (WFag ) and lower IGF-1 levels compared to whites. vWFag was inversely associated with IGF-1 and IGF-1/IGFBP-3 in blacks, with no associations found in whites. When patients with diabetes were included, the aforementioned associations found in blacks remained robust.